The Role of Teachers in Improving Fine Motor Skills of Early Childhood through Finger Painting Activities - Lutfiyah Uswatun Khasanah; Shofiama Mutma’innah; Annisa Mustaqimah; Fatika Salsabila; Elina Intan Apriliani (CV. Creative Tugu Pena, 2023)
This study explores teachers' professional role in improving children's fine motor skills through finger painting activities at RA Islam Irmassss. A descriptive qualitative approach was used to deeply understand this phenomenon. Data were collected through observations, interviews, and documentation of teachers and children involved in finger painting activities. The results showed that teachers have an important role in developing children's fine motor skills through finger painting, acting as facilitators, models, and mentors. Children show active participation and positive response to this activity. Teachers use a variety of creative teaching strategies to facilitate meaningful learning experiences for children. The implications of this study for educational practice include the improvement of teachers' teaching strategies in finger painting activities and their relevance to the early childhood education curriculum. The results of this study highlight the important role of teachers in supporting children's fine motor development and contribute to the development of more effective educational practices in early childhood education settings. Keywords: Fine Motor, Finger Painting, Early Childhood